Human resources management for health care organizations : a strategic approach - Pynes, Joan, 1957-; Lombardi, Donald N., 1956- (Jossey-Bass, 2011)
"This book offers an overview of human resource management in a health services or public health setting. Core concepts are covered including work and workplace assessment, motivators, HR planning and recruitment, decentralization, criteria-based position descriptions, performance appraisals, career ladder development and incentives. The book case studies that amplify a systems oriented approach to health services and strategies to improve retention. Regulatory and accreditation issues, organizational structure, management models, leadership, union management issues, innovative management models, and service issues that affect reimbursement, wage and practice in multiple settings are covered"--Resumé vydavatele
Keywords: zdravotnický management; personální management; zdravotnická zařízení; health service management; personnel management; health facilities; příručky; handbooks, manuals, etc